Exploring temporal information in neonatal seizures using a dynamic time warping based SVM kernel. (1st March 2017) - Ahmed, Rehan; Temko, Andriy; Marnane, William P.; Boylan, Geraldine; Lightbody, Gordon
Abstract: Seizure events in newborns change in frequency, morphology, and propagation. This contextual information is explored at the classifier level in the proposed patient-independent neonatal seizure detection system. The system is based on the combination of a static and a sequential SVM classifier. A Gaussian dynamic time warping based kernel is used in the sequential classifier. The system is validated on a large dataset of EEG recordings from 17 neonates. The obtained results show an increase in the detection rate at very low false detections per hour, particularly achieving a 12% improvement in the detection of short seizure events over the static RBF kernel based system.